STUDI PENGEMBANGAN KAWASAN KAMPUNG NELAYAN DI DESA SUMBER BENING KABUPATEN MALANG - Dedi, Dedi; Alfian, Rizki; Soelistary, Hesti Triana (Universitas Tribhuwana Tunggadewi, 2017)
The fishing village of Sumber Bening Village is a transitional area between terrestrial ecosystems and marine ecosystems that have a wealth of renewable resources managed into fisheries, marine and education areas. This study aims to determine the concept of development of the village area. This research is located in Sumber Bening Village, Bantur District, Malang Regency, East Java, this research was started from May - July 2017 and the method used was qualitative method with data retrieval in 3 ways: 1. Primary, 2. Secondary and 3. FGD and Total response questionnaire amounted to 30 people. Potentials that exist in the fishing village, among others, estuaries, mangrove tours and culinary tours. The concept of development in the village of fishermen in Sumber Bening Village is how to create a region of fishing village into a region that remains natural to stay awake by following the times. The concept of this planning is a model of recommendation drawing that will be adapted to Landscape character and potential in the area of fisherman's village such as: Access road, welcome area, sales of accessories, parking, lighting, additional facilities, mangrove tours, boat access road and breakwater. Kampung nelayan di Desa Sumber Bening merupakan daerah peralihan antara ekosistem darat dan ekosistem laut yang memiliki kekayaan sumberdaya yang dapat diperbaharui dan dikelola menjadi kawasan perikanan, bahari dan pendidikan. Penelitian ini bertujuan untuk menentukan konsep pengembangan kawasan kampung. Penelitian ini berlokasi di Desa Sumber Bening, Kecamatan Bantur, Kabupaten Malang, Jawa Timur, penelitian ini di mulai bulan Mei ? Juli 2017dan metode yang digunakan adalah metode kualitatif dengan pengambilan data dengan 3 cara : 1. Primer, 2. Sekunder dan 3. FGD dan Total respon kuisioner berjumlah 30 orang. Potensi yang ada di kampung nelayan antara lain, muara, wisata mangrove dan wisata kuliner. Konsep pengembangan di kawasan kampung nelayan di Desa Sumber Bening yaitu bagaimana cara menciptakan kawasan kampung nelayan menjadi kawasan yang tetap alami tetap terjaga dengan mengikuti perkembangan jaman. Konsep perencanaan ini berupa model gambar rekomendasi yang akan disesuaikan dengan karakter Lanskap dan potensi yang ada di kawasan kampung nelayan seperti : Akses jalan, welcome area, penjualan aksesoris, parkir, penerangan, penambahan fasilitas, wisata mangrove, akses jalan perahu dan pemecah ombak.